Developing a visual rhetoric conceptual framework for public service announcements (PSAs) advertising campaigns / Nur Safinas Albakry - Albakry, Nur Safinas (2016)
The visual rhetoric is an important element to increase the effectiveness of the process of information exchange. In fact, visual rhetoric helps to get messages across to the intended audience in a persuasive way. Visual rhetoric is described as a form of communication that uses images for creating meaning or constructing an argument. Hence, an analysis of visual rhetoric considers how images work alone and collaborate with other elements to create an argument designed for moving a specific audience Bulmer & Oliver (2006, p.55). Visual rhetoric in visual advertising involves how the audience choose to present information or argument through images. A key concept of visual rhetoric study in Malaysia Public Service Announcements (PSAs) contexts use focuses on how rhetorical figures in Public Service Announcements (PSAs) could convey to react and response in visual arguments by developing a persuasive message into a great communication process. The purpose of this study is to explore and discuss the understanding of rhetorical theories by implementing the visual rhetoric in print advertising on how visual arguments can affect consumers processing and response toward persuasive forms message. The aim of this study is to propose a framework system model for the effective use of visual content in the visual advertising communication process in Malaysia that could be employed by visual rhetoric in print media to instil advertising awareness. In order to strengthen and obtain the justifications of the model framework, the researcher utilised and adapted the various established theories and studies. Utilise post-test findings from the subject matter experts in the fields were also conducted to justify the effectiveness of the model framework. This allow people from various social culture to engage themselves in the activity of comprehending the message carried by the visuals displayed to them. The application is well-supported by psychological experiments and offer challenging extensions to advertising practices. This study is based on data obtained from interviews and survey questionnaires to evaluate the understanding of visual rhetoric analysis in Malaysia's advertising views with the objective to demonstrate the message and meanings into persuasive communication process strategies. This study proves that the engagement of visual semiotics can develop visual arguments by merging the rhetorical theories and cultural elements, and transforms the degree of persuasion tools as an effective communication process. Perhaps, this study will also spread knowledge on the usefulness of visual rhetoric in print advertising beyond aesthetic values as their presence accounts as beautiful crafts to the eyes of human. This research will also aid in opening new avenue for research platforms in rhetorical works for creative elements associated with effective advertising and ultimately to bridge cultural gaps in our social environment.